A comprehensive photovoltaic study on tungsten disulfide (WS2) buffer layer based CdTe solar cell - Emon E.I.; Islam A.M.; Sobayel M.K.; Islam S.; Akhtaruzzaman M.; Amin N.; Ahmed A.; Rashid M.J. (Elsevier Ltd, 2024)
Transition metal di-chalcogenides (TMCDs)-Tungsten disulfide (WS2) exhibit excellent optoelectronic properties such as suitable bandgap, high absorption coefficient, good conductivity, high carrier mobility, etc. to be used as a photovoltaic material for thin-film solar cells. In the present work, we have replaced the traditional buffer CdS and ITO/ZnO window layer in CdTe solar cells with the non-toxic, earth-abundant WS2 buffer and SnO2 window layer, respectively. The SCAPS-1D solar simulator is used to investigate the potentiality of WS2 as buffer material in CdTe solar cells. This numerical study provides a comparison of the performances between the proposed structure: SnO2/WS2/CdTe/Au and the baseline structure: ITO/ZnO/CdS/CdTe/Au. The impacts of the charge carrier generation rate, spectral response, current-voltage characteristics, bulk defect density, defect density at buffer/absorber interface, operating temperature, and capacitance-voltage characteristics on the solar cell performance parameters have also been analyzed. The tolerance level of defect density in WS2 bulk and WS2/CdTe interface are found to be 1017 cm?3 and 1012 cm?3, respectively. The temperature study reveals the poor structural robustness and thermal stability of the proposed cell. The conversion efficiency of the proposed cell has found to be 20.55% at the optimized device structure. Nevertheles, these findings may provide an insight to fabricate viable, environment friendly, and inexpensive CdTe thin-film solar cells. 2023